A STUDY OF PERCEPTIONS ABOUT CIGARETTES AMONG ADOLESCENTS IN BANJARNEGARA - Barni Barni; Ratih Subekti (Universitas Karya Husada Semarang, 2025)
Cigarettes remains a significant public health concern with broad health, social, and economic consequences. Despite continuous awareness efforts, smoking prevalence has not declined substantially, particularly among adolescents who represent a high-risk group. Research focusing on adolescent smoking is therefore essential to prevent long-term health and social harms and to inform evidence-based health, educational, and social interventions. This study applied a descriptive cross-sectional design involving 119 high school students selected through cluster random sampling. Data were collected using structured questionnaires and analyzed using univariate and bivariate methods with the Chi-square test. The findings indicated a nearly equal proportion of adolescents with smoking and non-smoking family members. Negative perceptions of smoking hazards were slightly more prevalent than positive perceptions, while most respondents perceived the implementation of Smoke-Free Areas in schools as adequate. Bivariate analysis demonstrated no significant association between family smoking behavior and adolescents’ perceptions of smoking (p = 0.360). These results underscore the need for comprehensive and collaborative prevention strategies involving families, schools, communities, and policymakers to reduce smoking initiation and protect adolescent health in the long term.